ANTI-AGING ACTIVITY WITH TYROSINASE INHIBITORS AND ANTIOXIDANTS FROM BADUY OUTER TRIBE PLANTS AS COSMETICS: REVIEW - Yuri Pratiwi Utami; Anto Apriyanto; Nurhayani; Agus Firmansyah; Firdaus (JURNAL KATALISATOR, 2025)
Aging is an unavoidable physiological process. The process of premature aging is prevented using natural anti-aging cosmetics derived from plants. Cosmetics can be used as anti-aging products. Therefore, plants can be used as substitutes for anti-aging chemicals with fewer side effects. There are many herbal plants that are empirically used by the Baduy community and have potential as anti-aging agents with tyrosinase inhibitory and antioxidant activities. Evidence of anti-aging activity can be obtained by testing the effects of each herbal plant, which has been conducted by several researchers previously. The purpose of this article is to provide information on which plants have the potential as anti-aging agents for cosmetic raw materials thru a literature review of journals in electronic databases. The results obtained from several plants such as Carica papaya L., Kaempferia galanga, Psidium guajava, Zingiber officinale var. Rubrum, Piper bettle, Caesalpinia sappan L, and Etlingera elatior (Jack) R.M. Sm have tyrosinase inhibitory activity. Orthosiphon stamineus B., Coleus scutellarioides (L.) Benth, and Imperata cylindrica (L) Beauv., the cogongrass plant, use an antioxidant approach as anti-aging. In conclusion, all herbal plants from the Baduy tribe have the potential as raw materials for anti-aging cosmetics